Change in Energy of Quasi Particles in Materials - Chanana, Ravi Kumar (European Journal of Applied Sciences, 2025)
This short communication reviews the change in energy of quasi particles in materials by providing the mathematical equations of differential calculus for the change in energy. These equations find applications in the Electron Physics related area of the Condensed Matter Physics. Photodiodes and Phototransistors are also proposed based on the finding of the intrinsic Fermi energy levels in semiconductors.